Quantitative assessment of BRAF V600 mutant circulating cell-free tumor DNA as a tool for therapeutic monitoring in metastatic melanoma patients treated with BRAF/MEK inhibitors. Issue 1 (December 2016) - Schreuer, Max; Meersseman, Geert; Van Den Herrewegen, Sari; Jansen, Yanina; Chevolet, Ines; Bott, Ambre; Wilgenhof, Sofie; Seremet, Teofila; Jacobs, Bart; Buyl, Ronald; Maertens, Geert; Neyns, Bart
Abstract Background BRAF V600 mutant circulating cell-free tumor DNA (BRAF V600mut ctDNA) could serve as a specific biomarker in patients withBRAF V600 mutant melanoma. We analyzed the value ofBRAF V600mut ctDNA from plasma as a monitoring tool for advanced melanoma patients treated with BRAF/MEK inhibitors. Methods Allele-specific quantitative PCR analysis forBRAF V600 E/E2/D/K/R/M mutations was performed on DNA extracted from plasma of patients with knownBRAF V600 mutant melanoma who were treated with dabrafenib and trametinib. Results 245 plasma samples from 36 patients were analyzed. In 16 patients the first plasma sample was obtained before the first dosing of dabrafenib/trametinib. At baseline, BRAF V600mut ctDNA was detected in 75 % of patients (n = 12/16).BRAF V600mut ctDNA decreased rapidly upon initiation of targeted therapy (p < 0.001) and became undetectable in 60 % of patients (n = 7/12) after 6 weeks of treatment. During treatment, disease progression (PD) was diagnosed in 27 of 36 patients. An increase of theBRAF V600mut ctDNA copy number and fraction, identified PD with a sensitivity of 70 % (n = 19/27) and a specificity of 100 %. An increase in theBRAF V600mut ctDNA fraction was detected prior to clinical PD in 44 % of cases (n = 12/27) and simultaneously with PD in 26 % of patients (n = 7/27). Conclusions Quantitative analysis ofBRAF V600mut ctDNA in plasma has unique features as a monitoring tool during treatment with BRAF/MEK inhibitors. Its potential as an early predictor of acquired resistance deserves further evaluation.